Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Asuransi Jiwa Bersama Bumiputera 1912 Jakarta - Wasilatun Nikmah; Henny Armaniah; Otto Siregar (Prisani Cendekia, 2022)
This study aims to determine the effect of work discipline and work environment either partially or simultaneously on the performance of employees of PT Asuransi Jiwa Bersama Bumiputera 1912. Sampling in this study used Slovin, namely 45 employees using the census method. Data collection methods used in this study using multiple linear regression analysis, F test, t test. The study results show that work discipline has a positive effect on employee performance at PT Asuransi Jiwa Bersama Bumiputera 1912 Jakarta. The work environment does not affect the performance of employees of PT Asuransi Jiwa Bersama Bumiputera 1912. Based on the results of the calculation of R2, it can be concluded that the work discipline and work environment variables are able to explain the variation or influence of the employee performance variable by 27.2%, this shows the work discipline and work environment variables effect on employee performance, while 72.8% is influenced by other variables not examined in this research.